2023
DOI: 10.3390/ma16093543
|View full text |Cite
|
Sign up to set email alerts
|

Improved Oxidation Resistance of Graphite Block by Introducing Curing Process of Phenolic Resin

Abstract: The purpose of this study is to improve the oxidation resistance of graphite blocks after graphitization at 2800 °C by introducing a curing process of phenolic resin, used as a binder to control the pore size. Using the methylene index obtained from FTIR, the curing temperature was set to 150 °C, the temperature at which cross-linking most highly occurs. Graphite blocks that had undergone curing, and were carbonized with a slow heating rate, showed increased mechanical and electrical properties. Microstructura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
(45 reference statements)
0
0
0
Order By: Relevance
“…However, to avoid any instability during the forming process, the maximum pressure was set to 130 MPa. A previous study by our research team reported the fabrication of carbon blocks under a pressure of 100 MPa [17]. In general, during low-pressure forming, it is challenging to achieve sufficient pressure-induced binding between coke and pitch.…”
Section: Raw Materials and Preparationmentioning
confidence: 99%
“…However, to avoid any instability during the forming process, the maximum pressure was set to 130 MPa. A previous study by our research team reported the fabrication of carbon blocks under a pressure of 100 MPa [17]. In general, during low-pressure forming, it is challenging to achieve sufficient pressure-induced binding between coke and pitch.…”
Section: Raw Materials and Preparationmentioning
confidence: 99%